The Impact of E-government on the Performance of Organizations: Analytical Study of the Opinions of a Sample of Officers and Employees of the General Traffic - Salman Mansi, Mustafa; Alwan Al-Taie, Faisal (Iraqi Journal for Administrative Sciences, 2023)
The aim of the study is to demonstrate the impact of "E-government" on the performance of organizations by highlighting the role of the General Traffic Directorate in the transformation field to achieve "E-government requirements. 156 officers & employees from 558 were chosen. From field-side, independent variable depended on "human resource, organizational flexibility, administrative support, appropriate technology"), while the dependent variable adopted the dimensions (“Improving work efficiency, service beneficiaries, employees’ satisfaction, organizational commitment”). The questionnaire was used as a basic tool for data collection according to the Fifth Likert Scale. The main hypothesis was (the existence of a significant impact/// relationship for the variable “e-government” with its dimensions in the variable of organizational performance with its dimensions). The statistical methods were relied on to analysis the practical side (“confirmative factor analysis, Cronbach’s alpha test, arithmetic mean, standard deviation, Pearson Correlation Coefficient, Structural Equation Modeling"). The study concluded: 1_The organization under study has an application for the requirements of "E-government" moderately at the level of implementing the tasks and functions assigned to it. 2_ It has good credit for qualified human capabilities in the field of technical work.